Physical, Chemical, and Morphological Characteristics of Bovine Hide Crackers in Acid Immersion - Dwi Wulandari; Ragil Yuliatmo; Thoyib Rohman Hakim,; Sugiyanto Sugiyanto (Hasanuddin University, 2026)
This study aimed to identify the effects of soaking time and acid type on the production of bovine hide cracker. The materials used were 6 kg bovine belly hide, 3% citric acid, and 3% acetic acid. The research employed a Completely Randomized Design (CRD) with a 2 × 3 factorial arrangement, consisting of two acid treatments (acetic and citric acids) and three soaking durations (0, 2, and 4 h). Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test when significant differences were observed. The results showed that the acid type significantly affected (P<0.05) the protein content, pH, swelling power, and color of bovine hide crackers but had no significant effect on the yield, taste, aroma, or crispiness. Soaking time significantly affected the yield, protein content, pH, swelling power, color, and taste, but did not significantly affect the aroma or crispiness. The yield values ranged from 21.20 to 30.32%, protein content from 60.33 to 78.30%, pH from 5.50 to 6.85, and swelling power from 632.30 to 2,838.46%. Based on organoleptic evaluation, the hide crackers exhibited a slightly brown color, slightly sour to non-sour taste, non-fishy aroma, and a crispy texture. Morphological observations revealed that soaking in an acidic solution produced thinner cell walls and more air cavities than the non-soaked treatment, thereby supporting an increase in the swelling power of the crackers. Soaking bovine hides with citric and acetic acids influenced the chemical, physical, and morphological characteristics of bovine hide crackers. The selection of acid type and soaking duration should be adjusted according to the desired product characteristics.